Problem-based Learning (PBL): Making an impact in education - Mohd Adnan, Nor Azila; Sim, Si Mui; Tan, C.P.L.; Alhady, S.F. (Faculty of Medicine, University of Malaya, 1999)
Problem-based learning (PBL) is an educational reform that is now becoming a household word in higher education, particularly in medical schools. Many medical schools have implemented a full problem-based learning curriculum (PBLC) While some have included PBL into selected units of the course in an otherwise conventional curriculum (embedded PBL) and others run their tutorials in a PBL manner within a modified conventional curriculum (hybrid curriculum). Yet there are others who claim that small components of PBL in a conventional curriculum are not PBL at all. Thus amateurs in the subject matter find difficulty in evaluating the logistics and outcome of these variations. This article focuses on the general characteristics of PBL and how this learning method can help enhance independent learning and critical thinking, whether in a full, embedded or hybrid curriculum. The extent of PBL to be included and which of the three types is to be adopted depends on the objective of the undergraduate medical course as determined by the faculty, resources available, limitations, feedback on the existing curriculum and various other factors.